Paternal High-Fat Diet Exposure Induces Adverse Effects on Offspring Health: a Systematic Review of Animal Studies - Gonçalves,Mariane dos Santos (2021)
Abstract This systematic review examined the effects of paternal exposure to a high-fat diet on the likelihood of offspring developing health consequences, including metabolic conditions. While the connection between a mother’s diet and offspring health has been well established, our understanding of whether offspring health is affected by a father’s diet remains limited. This systematic review was performed according to the Preferred Reporting Items for Systematic reviews and Meta-Analysis (PRISMA) recommendations. The PubMed, Scopus, and Embase electronic databases were searched using combinations of the MESH terms: obesogenic diet, high-fat diet, cafeteria diet, paternal diet, parental diet, programming, paternal effects, and paternal programming. Sixteen studies were selected after assessing articles for eligibility criteria. The main outcomes concerning offspring health related to metabolic disorders. The offspring of fathers exposed to a high-fat diet displayed elevated gene expression and serum levels of leptin, decreased gene expression and serum levels of adiponectin, insulin resistance, glucose intolerance, hyperglycemia, hyperinsulinemia, changes in the transcriptome of pancreatic islet tissues, increased triglycerides, and increased expression of lipogenic genes. The available evidence suggests that paternal exposure to a high-fat diet may induce harmful effects on the health of offspring.